Assessing Payne score accuracy through a bread wheat multi-genotype and multi-environment set from CIMMYT - Tabbita, Facundo; Ibba, Maria Itria; Andrade, Francisco; Crossa, José; Guzman, Carlos (Elsevier, 2024)
The Payne score is a prevalent strategy for assessing wheat quality by considering the distinct contributions of specific high-molecular-weight glutenin subunits. Despite its extensive use, the limited germplasm used in its development (84 British cultivars from the early 1980s) may limit its accuracy when is applied to other type of germplasm. Here we tested the Payne score accuracy and related scales using an extensive dataset. The precision of the scale is higher for Glu-A1 and Glu-D1 loci, particularly when predicting dough strength, and loaf volume. However, for dough extensibility, the accuracy decreased. For Glu-B1 it could discriminate differences to some extent, but higher scores did not always correspond to higher quality values, and vice versa. When the total Payne score was evaluated, the most pronounced degree of differentiation between scale values was observed for gluten strength related traits. When analyzing the total Payne score for various haplotypes, higher values for gluten strength, and loaf volume generally corresponded to higher Payne scores; however, some samples with low values were ranked with the highest scores and vice versa. Our findings suggest that there is a probability of selecting cultivars with high Payne scores that do not match the desired quality.